PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY OF ECLIPTA ALBA L. - M, Thenmozhi; M, JAYANTHI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Earlier various studies on pharmacological and therapeutic properties of Eclipta alba L. have been reported. The present investigation is on phytochemical screening and antioxidant activity of E. alba L. using different solvent extracts. Method: The shade-dried and grounded E. alba L. plant materials were treated with petroleum ether, chloroform, ethyl acetate, ethanol, methanol, and water (aqueous) solvents. The extracted residue was then dissolved in dimethylsulfoxide and further used for phytochemical screening and antioxidant studies. Results: E. alba L. on different solvent extract, the extractive yield was higher in methanol (14.22±0.99% w/w). The phytochemical screening analysis showed high number of secondary metabolites in the aqueous extract compared to other solvent studied. The metabolite flavonoids, phenols, and tannins are likely to be antioxidant potential compound. Hence, further, the total flavonoid content determination showed high of 0.875±0.020 μg/g in methanol extract. Further antioxidant property of E. alba L. was studied by method such as1,1-diphenyl-2-picrylhydrazyl radical scavenging activity, nitric oxide scavenging activity, metal chelating activity, and superoxide dismutase activity which showed high antioxidant potency with IC50 values of 62.76±0.63 μg/ml, 96.24±0.34 μg/ml, 72.29±0.61 μg/ml, and 108.40±0.52 μg/ml, respectively, in the petroleum ether extract. Conclusion: From the present study, the substantiate result of antioxidant studies has been obtained from petroleum ether extract . Furthermore the extractive value and flavonoid content was observed to be high in methanol extract. The antioxidant potency of E. alba L. was found to be high in petroleum ether extract compared to other solvent studied.